Cover Feature: Three‐Dimensional N‐doped Porous Carbon Derived from Monosodium Glutamate for Capacitive Deionization and the Oxygen Reduction Reaction (ChemElectroChem 24/2018). Issue 24 (16th November 2018) - Sun, Na; Zhang, Xian; Zhao, Cuijiao; Wang, Haojie; Lu, Haisheng; Kang, Shenghong; Zhou, Hongjian; Zhang, Haimin; Zhao, Huijun; Wang, Guozhong
Abstract : The Cover Feature shows a three‐dimensional N‐doped porous carbon (3D‐NPC) as an electrode material for both capacitive deionization (CDI) and Zn–air batteries. Zn–air batteries can be used to drive the desalination of CDI. It will pave the way for developing energy‐integrated CDI technology to expand its portable adhibition. More information can be found in the Article by N. Sun et al. onpage 3873 in Issue 24, 2018 (DOI:10.1002/celc.201801063 ).